Exploring Body Composition of Pre-adolescent Schoolers based on Skinfold Thickness and Arm Girth for Assessing Anthropometry - Rahman, Sharmin; Tanjin, Rokhsana; Binte, Nazia; Naher, Nurun; Khan, Mohammad Adnan; Amin, Sanjida (The Journal of Ad-din Women’s Medical College, 2024)
Background: Early nutrition plays a pivotal role in shaping long-term health and well-being during adulthood and beyond. Nevertheless, there has been limited exploration into methods for assessing the nutritional status of Bangladeshi pre-adolescent schoolers through anthropometric measurements, encompassing weight, height, skinfold thickness, circumferences (such as head and waist), and limb lengths (including shoulder and wrist). Evaluating nutritional conditions using these measurements reveals variations among deferent groups, such as boys versus girls and distinctions between rural and urban areas. Part of this study have been adopted from earlier 4 studies but on extrapolating data from the database of Anthropometric Somatotype of Government Primary School Children in Dhaka City. Materials & Methods: A descriptive cross-sectional study was conducted among 400 government elementary school students aged between 9 and 12 years. Data was collected using a semi-structured questionnaire and analyzed using SPSS. Findings: Percentage of body fat, total body fat & skinfold thickness of the groups of boys were higher than same age group of girls. Girls BMI ranges are higher than the same age group of boys. In the matter of Body Surface Area, girl child of 9 year has less BSA than 9year age boys, as age goes up the scenario changes gradually. 9–10-year-old boys have higher Arm grith than those age of girls, 10-12 years old girls tend to have higher calf grith than boys of same age group. The Journal of Ad-din Women's Medical College; Vol. 12 (1), Jan 2024; p 15-23